An enlarged cell wall proteome of Arabidopsis thaliana rosettes. Issue 24 (December 2016) - Hervé, Vincent; Duruflé, Harold; San Clemente, Hélène; Albenne, Cécile; Balliau, Thierry; Zivy, Michel; Dunand, Christophe; Jamet, Elisabeth
Abstract : Plant cells are surrounded by cell walls playing many roles during development and in response to environmental constraints. Cell walls are mainly composed of polysaccharides (cellulose, hemicelluloses and pectins), but they also contain proteins which are critical players in cell wall remodeling processes. Today, the cell wall proteome of Arabidopsis thaliana, a major dicot model plant, comprises more than 700 proteins predicted to be secreted (cell wall proteins—CWPs) identified in different organs or in cell suspension cultures. However, the cell wall proteome of rosettes is poorly represented with only 148 CWPs identified after extraction by vacuum infiltration. This new study allows enlarging its coverage. A destructive method starting with the purification of cell walls has been performed and two experiments have been compared. They differ by the presence/absence of protein separation by a short 1D‐electrophoresis run prior to tryptic digestion and different gradient programs for peptide separation before mass spectrometry analysis. Altogether, the rosette cell wall proteome has been significantly enlarged to 361 CWPs, among which 213 newly identified in rosettes and 57 newly described. The identified CWPs fall in four major functional classes: 26.1% proteins acting on polysaccharides, 11.1% oxido‐reductases, 14.7% proteases and 11.7% proteins possibly related to lipid metabolism.